Psychosocial and emotional factors that impact the academic performance of university students - Brito-Cruz, Teresa del Jesús; Torres-Zapata, Ángel Esteban; Zarza-García , Addy Leticia; Moguel-Ceballos, Juan Eduardo; Villanueva-Echavarría , José Rafael (Revista Multi-Ensayos, 2025)
Currently, anxiety, stress and burnout are considered psychosocial and emotional factors that strongly influence the academic performance of university students, in addition to the environment through external factors related to family support and the development of economic activities to support education, these variables generate an impact on the motivation and emotional well-being of students, some research determines that not precisely these variables can correlate with academic performance in a significant way, however anxiety and stress influence the quality of learning and this contributes to school dropouts, to face the onslaught of these variables it is necessary to develop socio-emotional skills, strengthen self-esteem and establish strategies for the adequate management of stress, therefore, it is an imperative need to develop intervention programs aimed at the care of mental health through psychological support, jointly developing preventive strategies to address these factors and thus promote the improvement of performance and academic performance as well as the integral development of students through the exercise of psychological and emotional well-being.